Economy, politics, and critical events: From transformation to permanent crisis - Simone Polillo (economic sociology. perspectives and conversations, 2024)
Events, ruptures, critical junctures: these have become critical concepts in sociology. Yet, they have not enabled current models to grasp the complexity of capitalist crises, in their dual nature as unique occurrences and intrinsic characteristics of capitalist economies. Studies of political crises, where these concepts have been developed most fully, make political conflict, semiotics, and cultural change central to understanding the contingencies and emergent properties of crises and their fragile connection to the underlying reality they represent.
Keywords: 300